Ecological Economics. Towards an Ecology in Teaching of Economics - Rodríguez Gama, German (2019)
The Ecological Economics is an alternative that respond to the debts that the traditional economics has historically ignored. The students’ movements around the world demand a deep reform in the education of economy to attend the greatest crisis we face as humanity: the sustainability of life.In this text, we briefly review the way in which the traditional economy has approached the issues associated with the environment, the challenges and limitations and presents the Ecological Economics as an alternative that extracts from the transdisciplinarity.